2013
DOI: 10.1111/j.1532-7795.2012.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Family Obligations and Educational Goals Among College‐Enrolled Youth on Jeju Island, Korea

Abstract: This survey study examined the role of parents in the educational goals of 265 college-enrolled youth (19-27 years; M = 22 years; 64% female students) on Jeju Island, Korea. A model of shared agency was applied to identify the processes through which associations between family assistance and adjustment can be explained. Four factors of parental educational involvement were found: coactivity (consisting of autonomy support and collaboration), accommodation, noninvolvement, and directing. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Within developmental psychology, FOB have been portrayed as embedded within collectivistic cultures (Chang, 2013; Fuligni et al, 1999). The research literature surrounding FOB has found that these values correlate positively with the outcomes of college students from collectivistic cultures, in this case, Korea, and are mediated by parental support for self-determination (Chang, 2013). What has remained uncertain was whether FOB would correlate positively with the outcomes of college students from more individualistic cultures, such the dominant culture of Americans of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within developmental psychology, FOB have been portrayed as embedded within collectivistic cultures (Chang, 2013; Fuligni et al, 1999). The research literature surrounding FOB has found that these values correlate positively with the outcomes of college students from collectivistic cultures, in this case, Korea, and are mediated by parental support for self-determination (Chang, 2013). What has remained uncertain was whether FOB would correlate positively with the outcomes of college students from more individualistic cultures, such the dominant culture of Americans of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Although the creators of SDT present it as reflecting universal needs, processes, and consequences, the applicability of SDT to Koreans has been regarded as uncertain because Korean parents have been characterized as highly involved in the lives of their children (Kwon et al, 2016), much more involved than what is considered normal in the U.S. Korean parenting is based on cultural values and traditions that prioritize connectedness and intimacy within the family, with strong emphasis placed on respect for hierarchy and the elderly (Chao, 1994; Chung et al, 2007; Hwang, 1999; Raymo et al, 2015; Ryu, 2007). In addition, Korean culture strongly values family obligations, consisting of respect for family, as well as support for family members, both in the present and the future (Chang, 2013).…”
Section: Korean Parentingmentioning
confidence: 99%
“…Since kirogi youth's educational goals can be considered a family project, parents may be more motivated to ensure that their youth's educational activities are to their satisfaction. Thus, we refer to a model of shared and non-shared agency that considers the goal engagement of the parent and the youth at the same time (Chang, 2013;Chang et al, 2010). This model was applied in order to understand parenting behaviors more accurately -as they occur within the parent-child relationship, which during adolescence is more mutual and bidirectional than in childhood.…”
Section: Shared Agency With Youth For Educational Goalsmentioning
confidence: 99%
“…In particular, cultural differences may be present in the acceptability of parental authority and the adaptiveness of parental directing given Confucian-influenced values and beliefs (Luo et al, 2013). However, it is hypothesized that maternal collaboration would be the most effective role for parents within the kirogi family context due to the investment of parents in children's education and the necessity of youth to have and regulate their own educational goals (Chang, 2013;Wigfield & Eccles, 2000).…”
Section: Shared Agency With Youth For Educational Goalsmentioning
confidence: 99%
See 1 more Smart Citation